CURRENT ISSUES OF THE OCCUPATIONAL HEALTH OF PASSENGER VEHICLE DRIVERS IN THE CONDITIONS OF HOT CLIMATE - B.KH. NUSHERVONI; A.B. BABAEV (Avicenna Tajik State Medical University, 2018)
The article contains data on the impact of factors of the working environment and labour process on the health status of drivers of passenger vehicles and incidence rates with a temporary disability. Based on the research, the authors note that drivers of buses and trolleybuses are exposed to various physical and chemical factors in combination with factors of the labor process. It is noted that drivers perform very intense work, depending on the degree of traffic intensity in large cities. In addition, they must, according to the schedule, abide by a rigid mode of time around the city. Drivers are responsible for the safety of passengers, and other road users, which leads to a significant psychological stress. Many drivers complain about an overtime work, increasing to 10-11 hours a day. At the same time, in the air of workplaces the content of carbon monoxide and nitrous oxide is noted, the number of which in many cases exceeds their maximum permissible concentration. Analysis of the literature suggests that the features of the labour of drivers of passenger vehicles when working in hot climates and congestion of urban highways are not well understood.